Physicochemical, spectral, molecular docking and ADMET studies of Bisphenol analogues; A computational approach. (2021) - Uzzaman, Monir; Hasan, Md. Kamrul; Mahmud, Shafi; Yousuf, Abu; Islam, Saidul; Uddin, Mohammad Nasir; Barua, Ayan
Abstract: Bisphenols are widely used in polymer and packaging industries. But they are contaminating the environment and food chain by degradation, particularly affecting to the human endocrine system. Herein, we have investigated the physicochemical, spectral, biological and pharmacokinetic properties of some selected bisphenol analogues utilizing computer-aided drug design methods. Geometry optimization has been performed by employing density functional theory with B3LYP/6-311g++ (d, p) basis set. Geometrical, thermodynamical, molecular orbital and electrostatic potential studies have been calculated to investigate their physical and chemical behavior. Meanwhile, FT-IR, Raman and UV-Vis's spectra have been measured and compared with the experimental values. Molecular docking and dynamics simulation studies have been performed against human estrogen-related receptor protein to investigate their binding affinity, mode and interactions with the receptor. ADMET prediction has been performed to compare their absorption, distribution, metabolism and toxicity. Among the studied analogues, Bis AF has the highest free energy and Bis E has highest binding affinity. Meanwhile, Bis S shows the highest dipole moment and the chemical reactivity. Most of them have inhibitory property to the CYP2C9 and Bis S shows the carcinogenic property. Based on the comparative physicochemical, spectral, biological and ADMET calculation, this study can be helpful to understand more deeply about their biochemical impact on the environment and human being. Graphical abstract: Image 1